Mud Crab Aquaculture and Biology : (Australian centre for International Agricultural Research, 1999)
Mud crabs have only been reared from stock captured from the natural environment, in those countries where they are being farmed. Now, as reported in these Proceedings, larval production of mud crabs can be reliably achieved, the rapid growth of mud crabs identified and their taxonomy clarified. The commercial implications of this successful research are enormous, as are the implications for preserving the natural resources of the world's fisheries.